Melting processes of two dimensional confined colloids interacting via a quasi-square well potential - Jungmann, Rafael Magalhães (2018)
In this M.Sc. dissertation we implement Brownian dynamics to investigate the melting pro- cesses of colloidal particles confined isotropically with competing interactions represented by a potential tailored in a repulsive-attractive-repulsive fashion as the inter-particle distance in- creases. The stable configurations of such system is composed of a large diversity of structures, which includes quasi-crystalline, triangular, square, and mixed orderings, as well as, the pres- ence of ornamental patterns such as fringes and holes, which are located, respectively, at the border and interior of the clusters. Our molecular dynamics simulations demonstrate that dur- ing the melting process particles are able to swing between some different micro phases. We also tested the fringes stability which demonstrated to be higher than the one found in compact clusters. Finally, we show that, at the high temperature regime, the system loses its angular ordering while still preserves its radial inter-particle confinement, which, ultimately, causes the proliferation of small sub-clusters.